2015
DOI: 10.1021/acsbiomaterials.5b00401
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Fillers for Dental Resin Composites: Present and Future

Abstract: Dental resins represent an important family of biomaterials that have been evolving in response to the needs in biocompatibility and mechanical properties. They are composite materials consisting of mostly inorganic fillers and additives bound together with a polymer matrix. A large number of fillers in a variety of forms (spheroidal, fibrous, porous, etc.) along with other additives have been studied to enhance the performance of the composites. Silane derivatives are attached as coupling agents to the filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
119
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(129 citation statements)
references
References 155 publications
0
119
0
10
Order By: Relevance
“…Excellent, in depth reviews focusing specifically on the filler technology can be found in the literature [1214], and a summary is provided here. Microfill composites contain colloidal silica particles with average size of 50 nm.…”
Section: The Evolution Of Filler Systemsmentioning
confidence: 99%
“…Excellent, in depth reviews focusing specifically on the filler technology can be found in the literature [1214], and a summary is provided here. Microfill composites contain colloidal silica particles with average size of 50 nm.…”
Section: The Evolution Of Filler Systemsmentioning
confidence: 99%
“…Inorganic fillers, such as silicon dioxide, quartz in its crystalline state, aluminium oxide (Al2O3), titanium dioxide (TiO 2 ), zinc oxide (ZnO), and zirconium oxide (ZrO 2 ), that are easy to handle but not immune from marginal degradation during time and the consequent gap formation between the tissue/material interface [46].…”
Section: Restorative Approaches To Pathological Alterationsmentioning
confidence: 99%
“…The roles of the filler involve enhanced mechanical performance including properties such as hardness, strength, and wear resistance, along with improved biocompatibility and moisture resistance [3,5] as well as reduced thermal expansion coefficient and polymerization-induced volumetric shrinkage that leads to significant stress [6]. However, extensive filler loading in resin-based composites can hinder photopolymerization kinetics due to light scattering and also influence handling properties due to the substantial increase in initial viscosity of the uncured composite paste as compared to the unfilled resin [7]. Therefore, the influence of filler types, shapes, sizes, concentrations, and functionalization on kinetics, mechanics, rheology, biocompatibility, and handling properties of resin-based composites has been investigated widely in the search for a more durable and practical dental restorative composite material [1,812].…”
Section: Introductionmentioning
confidence: 99%
“…Different classifications of inorganic fillers include metal oxides (eg: silica, aluminum oxide, titanium dioxide), alkaline silicate glass, bioactive or biomimetic fillers (eg: hydroxyapatite), and organic-inorganic hybrids [7]. Silicon dioxides are often utilized in resin-based dental composites [11] due to their mechanical performance along with reduced water-sorption and solubility [7].…”
Section: Introductionmentioning
confidence: 99%